Fostering Consumer Loyalty through Green Marketing: Unveiling the Impact of Perceived Value in Malaysia’s Retail Sector - Krishnan, Vijayaletchumy; Nusraningrum, Dewi; Prebakarran, Praveena Nair; Wahid, Siti Daleela Mohd (Journal of Ecohumanism, 2024)
This study investigates the impact of green marketing strategies on consumer loyalty within the Malaysian retail sector, with a focus on the mediating role of perceived value. As global emphasis on sustainability increases, green marketing has become a crucial strategy for retailers aiming to attract eco-conscious consumers. This research explores how effectively implemented green marketing strategies can influence consumer behavior and enhance consumer loyalty by increasing perceived value. Employing a quantitative research design and using Smart PLS for data analysis, the study involves a sample of Malaysian consumers. The findings reveal that green marketing strategies positively and significantly influence perceived value, which, in turn, significantly impacts consumer loyalty. Mediation analysis confirms that perceived value partially mediates the relationship between green marketing strategies and consumer loyalty, underscoring its crucial role. The results highlight the importance of communicating the environmental benefits and sustainability of products to enhance perceived value and foster stronger consumer loyalty. For retailers, these insights provide actionable guidance on leveraging green marketing strategies to build a loyal customer base in a competitive market. The study contributes to theoretical understanding of green marketing’s impact on consumer behavior and offers practical implications for retail businesses aiming to integrate sustainability into their core strategies. Limitations include the cross-sectional design, which restricts causality determination, and the focus on the retail sector, which may limit generalizability. Future research should consider longitudinal studies, cross-cultural comparisons, and additional mediators and moderators to provide a more comprehensive understanding of the dynamics involved. Overall, this research highlights the significant role of green marketing strategies and perceived value in fostering consumer loyalty, offering valuable insights for retailers in the Malaysian context.